EFEKTIVITAS MANAJEMEN PROGRAM PARENTING TERHADAP KOLABORASI DAN KEPUASAN ORANG TUA DI PAUD - Ni Komang Theda Febrina Subagia; Christiani Endah Poerwati (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
Optimal early childhood development requires strong synergy between parents and early childhood education institutions, although parenting program management still faces various challenges. This study aims to evaluate the effectiveness of parenting program management in strengthening collaboration between parents and early childhood education institutions and its implications for parental satisfaction. This study employed a mixed methods approach with an explanatory sequential design. Quantitative data were collected from 66 parents and 5 teachers through questionnaires, while qualitative data were obtained through interviews and Focus Group Discussions (FGDs). The results indicate that parenting program management is categorized as highly effective (82,80% based on parents’ assessment; 84.60% based on teachers’ assessment). Systematic program management strengthens collaboration between schools and families, which contributes to increased parental satisfaction as a form of perceived program effectiveness. The novelty of this study lies in integrating program management, parent–institution collaboration, and parental satisfaction into a comprehensive evaluation framework, resulting in an applicable partnership-based parenting program management model.